Quantification of urinary sodium concentrations in term infants. (March 2019) - Cullis, Paul S; Cull, Frith; Bruce, Gordon; Johnston, Allan; Patel, Hetal; Jackson, Lesley; Galloway, Peter; Walker, Gregor
Background: Infants with gastrointestinal conditions and poor weight gain are administered sodium supplementation based on urinary sodium concentrations. However, the reference range of urinary electrolytes is unknown. The aim of this study was to ascertain the normal values of urinary electrolytes in healthy, term infants. Secondary aims were to establish the relationship between urinary electrolytes with weight velocity and feeding practices. Methods: Healthy, term (≥37 weeks' gestation) infants were recruited. Parental questionnaires were completed before discharge and at six weeks. Electrolytes were quantified from a urine sample at six weeks. t-Tests and Mann-Whitney U tests were conducted for parametric and non-parametric electrolytes, respectively. Results: A total of 200 infants were recruited before discharge. Twenty-nine follow-up questionnaires and urine samples were returned (nine female; mean gestational age 39 + 6 weeks [SD 9.9 days]; mean birthweight 3350 g [SD 483 g]; 17 breastfed, nine formula and three mixed; mean change in Z score for weight –0.914 [SD 0.814]). Majority (25/29) of infants had urinary sodium <20 mmo/L. Change in Z score for weight was similar between infants with sodium <20 mmol/L and >20 mmol/L ( P = 0.78). All exclusively breastfed infants had sodium <20 mmol/L, however, not statistically dissimilar to formula-fed infants ( P = 0.27). Conclusion: Most term infants in this study had urinary sodium values <20 mmol/L with no identified relationship to weight velocity. Lower concentrations of sodium could be not quantified reliably because of the limitations of the analytical method that were used. More evidence is required to identify candidates for sodium supplementation.